PENGARUH LITERASI KEUANGAN TERHADAP PERILAKU PENGELOLAAN KEUANGAN MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI - Silviana Veriwati; Dessy Triana Relita; Emilia Dewiwati Pelipa (STKIP Persada Khatulistiwa Sintang, 2021)
This study aims to determine the effect of financial literacy on the financial management behavior of students in economic study programs. Tehe research is a quantitative research. The population in this study were 106 students of the economic study program STKIP Persada Khatulistiwa Sintang. The number of sampel of this study were 84 respondents, the sampling technique used was random usig the Slovin formula. First, data analysis was done by looking for validity and reliability, descriptive analysis test, contribution test, and classical assumption test. The data obtained were processed with the SPSS version 18 program. The results showed that financial literacy had an effect on the financial management behavior of students in the economic education study program of STKIP Persada Khatulistiwa Sintang, with the results of the t test, the t count was 5,119 greater than (>) t table 1.988 and the value os Sig. 0.000 < 0.05